PENGARUH PERCEIVED QUALITY DAN PRICE DISCOUNT TERHADAP LOYALITAS PELANGGAN PADA APLIKASI GRABFOOD : (Studi pada Pengguna GrabFood Kota Medan) - Hasibuan, Febriyanti; Dirbawanto, Nana Dyki (Transpublika Publisher, 2024)
The high demand for food and beverage consumption by the public has become a business opportunity which PT Grab Indonesia has realized by opening the Grabfood service feature, which is an online food and beverage delivery service feature. Grabfood's rapid development cannot be separated from PT Grab Indonesia's ability to attract customers, such as providing a perceived quality experience for customers and providing price discounts to create customer loyalty. This study aims to determine how the effect of perceived quality and price discount on Grabfood customer loyalty in Medan City on the Grab application. The research method used in this research is quantitative. The population in this study were Grabfood customers, the sample was determined to be 100 respondents with a sampling technique using purposive sampling. The results of this study indicate that perceived quality and price discount have a significant effect on customer loyalty. The results of this study indicate that perceived quality (X1) and price discount (X2) have a significant effect on customer loyalty (Y). Based on the results of the determination test, it is obtained that the Adjusted R Square value is 0.296 (29.6%) the perceived quality and price discount variables simultaneously have an influence of 29.6% on the dependent variable customer loyalty. while the rest is influenced by other variables not examined in this study.